Penguatan Karakter Anggota ‘Aisyiyah Melalui Penyuluhan Nilai-nilai Hijrah Rasulullah - Casmini Casmini (Universitas Muhammadiyah Semarang, 2020)
Strengthening the character through the promotion of the values of the Prophet's migration was carried out as a responsive form of PP 'Aisyiyah Tabligh Assembly to the dynamics of globalization in an effort to member' Aisyiyah who is not a phobia and has resistance to the development of information technology but still holds firmly the values of the hijrah experienced by Rasulullah . Strengthening these character values is carried out through counseling with the recitation model in the monthly recitation in October 2019. The reinforcement results show that the counseling participants understand the values of the Prophet's migration which underlies the strength of personal character and as a member of the isy Aisyiyah organization in developing da'wah. Implementation of character values need to follow the Prophet migrated more intensive training on leadership twig 'Aisyiyah respectively.